Adaptation Decorative Images as Background Imageson the Design Application - Maulana A., Deden; M. , Benyamin Firdaus (International Journal of Psychosocial Rehabilitation, 2020)
The treasures of ethnic images scattered in various regions in Indonesia are cultural values, as real wealth that can be used as an inspiring source and can be developed for diversity of decoration. It can be said that Indonesia is one of the countries with a high level of cultural diversity or a high level of heterogeneity, so it is very natural to emerge various visual works in the form of decoration. Decorative motifs are decorative or decorative ornaments with visualized manifestations with various patterns aimed at beautifying a container. Decorative motifs can be placed on a flat surface, either on a two-dimensional surface or a three-dimensional plane that has depth. There are several types of decoration or motifs that manifest as imitations of nature (nature) or geometric shapes and elements of pigur or simplification of human images (figurative) to visualize a meaning.While the background image (background) in a graphic design item can be said as a visual reinforcement image with the aim to give emphasis or a visual binder in a series of media designs. Usually the background image is used for uniformity of items in media promotion activities. In the background image there are several elements; usually there are elements of fields, lines, points, and ethnic images that are strengthened by harmonious color unity. As the most prominent illustration in the background there is in the packaging design, such as a background image that displays landscape illustrations, product illustrations, color blocks (color flat) or shapes (shapes) arranged with a combination of several other elements, this background image is processed by technical means photographically or using a computer.The purpose of this research activity, how to design a background image by using the elements of ethnic images, can act as a treasure to enrich the development of imaging of an item or media design of a design. The research model is carried out by means of an experimental model approach that can be done by students in order to understand a way, process, and technique in developing ethnic images. The stages of the study were carried out with several stages of experimental case studies on the data that came with a simple image. Ethnic images were chosen according to the observation level of the uniqueness of the motifs, accompanied by a brief narrative about the cultural background of the region, which was considered to be representative of the design basis. Before starting the experiments, the students conducted group discussions with a basic model of the problem approach (problem-based learning), discussion (focus group discussion), and presentations. This research activity is expected to be able to open up knowledge about insights into ornamental variations as a source of data that can be developed as a basis for the design of work activities. Students gain experience by observing, discussing, and executing in making designs on background images as identity images that can visually reinforce messages.